2012
DOI: 10.1080/09205063.2012.735100
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of inflammatory reaction in the use of purified alginate microcapsules

Abstract: Alginate, a polysaccharide extracted from brown seaweed, remains the most widely used biomaterial for immobilizing cells to be transplanted, because of the good viability of the encapsulated cells and the relatively ease of processing for cell encapsulation. However, the main drawback is the immune reaction in vivo. To overcome this problem, we have demonstrated a modified Korbutt method for alginate purification. After alginate microcapsules were manufactured, NIH/3T3 fibroblast cells were seeded in purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Our findings demonstrated that both EMBs and HMBs did not elicit immune activation in vitro . This is probably due to ultrapure sodium alginate being used and is consistent with other studies testing inflammation and immune reaction related to the purity of alginate [12] , [32] . Rokstad et al (2011) showed that alginate microbeads are complement compatible [33] .…”
Section: Discussionsupporting
confidence: 89%
“…Our findings demonstrated that both EMBs and HMBs did not elicit immune activation in vitro . This is probably due to ultrapure sodium alginate being used and is consistent with other studies testing inflammation and immune reaction related to the purity of alginate [12] , [32] . Rokstad et al (2011) showed that alginate microbeads are complement compatible [33] .…”
Section: Discussionsupporting
confidence: 89%
“…8). Although previous reports have shown that alginate has immunomodulatory functions (3,17), we believe that our study is the first to thoroughly investigate the mechanisms of how alginate-derived oligosaccharides improve the host defense against bacterial infection.…”
Section: Discussionmentioning
confidence: 96%
“…The main methods for inhibiting cell adhesion have included the use of optimizing materials, which change or modify the surface properties of the microcapsules, and screening the transplantation site. For example, microcapsules made from purified alginate materials have a longer lifespan than nonpurified alginate microcapsules coated with (short‐chain alginate)‐ co ‐MPEG have a longer lifespan than conventional alginate, and microcapsules transplanted into the bone marrow survive longer than those transplanted under the kidney capsule . In these studies, the extent of cell adhesion was determined by examining tissue sections from biopsies of the enwrapped microcapsules explanted after implantation.…”
Section: Introductionmentioning
confidence: 99%